Unveiling the fungal mycobiota present throughout the cork stopper manufacturing process - Barreto, Maria C; Houbraken, Jos; Samson, Robert A; Brito, Dulce; Gadanho, Mário; San Romão, Maria V (FEMS Microbiology Ecology, 2012)
A particular fungal population is present in the main stages of the manufacturing process of cork discs. Its diversity was studied using both dependent (isolation) and independent culture methods (denaturing gel gradient electrophoresis and cloning of the ITS1-5.8S-ITS2 region). The mycobiota in the samples taken in the stages before and after the first boiling seems to be distinct from the population in the subsequent manufacturing stages. Most isolated fungi belong to the genera Penicillium, Eurotium and Cladosporium. The presence of uncultivable fungi, Ascomycota and endophytes in raw cork was confirmed by sequencing. The samples taken after the first boiling contained uncultivable fungi, but in a few samples some isolated fungi were also detected. The main taxa present in the following stages were Chrysonilia sitophila, Penicillium glabrum and Penicillium spp. All applied techniques had complementary outcomes. The main factors driving the shift in cork fungal colonization seem to be the high levels of humidity and temperature to which the slabs are subjected during the boiling process.
Keywords: Biodiversity; cloning; Cork; denaturing gel electrophoresis; Denaturing Gradient Gel Electrophoresis; DNA; Fungal; Fungal: genetics; fungi; Fungi: classification; Fungi: isolation & purification; humidity; Industry; Metagenome; mycobiota diversity; Penicillium; Penicillium: classification; Penicillium: isolation & purification; phylogeny; Plant Bark; Plant Bark: microbiology; Portugal; Quercus; Quercus: microbiology; Ribosomal Spacer; Ribosomal Spacer: genetics; Spain; Temperature; uncultivable fungal species

Prediction of near-surface soil moisture at large scale by digital terrain modeling and neural networks. - Lavado Contador, J F; Maneta, M; Schnabel, S (Environmental monitoring and assessment, 2006)
The capability of Artificial Neural Network models to forecast near-surface soil moisture at fine spatial scale resolution has been tested for a 99.5 ha watershed located in SW Spain using several easy to achieve digital models of topographic and land cover variables as inputs and a series of soil moisture measurements as training data set. The study methods were designed in order to determining the potentials of the neural network model as a tool to gain insight into soil moisture distribution factors and also in order to optimize the data sampling scheme finding the optimum size of the training data set. Results suggest the efficiency of the methods in forecasting soil moisture, as a tool to assess the optimum number of field samples, and the importance of the variables selected in explaining the final map obtained.
Keywords: Biological; Dehesa; forecasting soil moisture; humidity; Models; Neural Networks (Computer); sampling; Soil; topographic variables

Modificación del microclima edáfico producido por riegos en forestaciones de zonas semiáridas - Jiménez, M N; Ripoll, M A; Navarro, F B (Investigación agraria. Sistemas y recursos forestales, 2004)
In this work, we analyse the effect that the irrigation carried out in different times during the summer drought produces on the edaphic microclimate over holm oak plants (Quercus rotundifolia) in abandoned agricultural soils of continental semiarid climate. The study has been done over 5 plots of 60 plants each, located in the high plateaux of Rambla Becerra (Guadix-Granada), in which it has been accomplished a continuation of the survival rate and development after the planting during two years (2001-2002). The answer of the plant to its new medium was excellent in all the irrigated plots, whereas in the witness plot (without irrigation) the survival is considerably inferior. The height of the holm oaks in those plots with any kind of irrigation is significantly superior than the ones in the witness plot, and the diameter of the holm oaks of the plots which receive continuous summer irrigation shows significant differences with respect to the rest of the plots. The bioclimatic diagrams achieved in each plot reflect relevant differences; the summer irrigation reaches to reduce the drought period and even, in the plot that receives the continuous summer irrigation, this is eradicated, thus generating a new period of vegetation activity. The humidity of the soil shows significant differences, being the plot number 8, which is continually being irrigated, the only one that keeps the humidity in depth. The hydric deficit diminishes punctually in the plots irrigated only once, whereas in the parcel n. 8 diminishes drastically with the following increase in the vegetation activity.
Keywords: agricultural; bioclimatic diagrams; humidity; microclimate; Soil

Modificación del microclima edáfico producido por riegos en forestaciones de zonas semiáridas - Jiménez, M. N.; Ripoll, M. A.; Navarro, F. B. (Investigación agraria. Sistemas y recursos forestales, 2004)
In this work, we analyse the effect that the irrigation carried out in different times during the summer drought produces on the edaphic microclimate over holm oak plants (Quercus rotundifolia) in abandoned agricultural soils of continental semiarid climate. The study has been done over 5 plots of 60 plants each, located in the high plateaux of Rambla Becerra (Guadix-Granada), in which it has been accomplished a continuation of the survival rate and development after the planting during two years (2001-2002). The answer of the plant to its new medium was excellent in all the irrigated plots, whereas in the witness plot (without irrigation) the survival is considerably inferior. The height of the holm oaks in those plots with any kind of irrigation is significantly superior than the ones in the witness plot, and the diameter of the holm oaks of the plots which receive continuous summer irrigation shows significant differences with respect to the rest of the plots. The bioclimatic diagrams achieved in each plot reflect relevant differences; the summer irrigation reaches to reduce the drought period and even, in the plot that receives the continuous summer irrigation, this is eradicated, thus generating a new period of vegetation activity. The humidity of the soil shows significant differences, being the plot number 8, which is continually being irrigated, the only one that keeps the humidity in depth. The hydric deficit diminishes punctually in the plots irrigated only once, whereas in the parcel n. 8 diminishes drastically with the following increase in the vegetation activity.
Keywords: agricultural; bioclimatic diagrams; humidity; microclimate; Soil